Pacific Alliance as a platform for Peru to increase its economic relations with Asia - Aquino Rodríguez, Carlos Alberto (2015)
The present article review the Pacific Alliance as an agreement that has more possibilities to succeed in Latin America given that their members share many similarities in economic policies and in its openness to foreign trade. The potential of the Pacific Alliance as a common platform to increase exports to Asia, especially for nontraditional goods, is analyzed. Also what should be done to reach that objective is considered.